Kimia Hidrokarbon dalam prespektif al-Quran - Isnaini, Nufia Rohmatul (Maliki Interdisciplinary Journal, 2023)
Chemistry, especially hydrocarbons, can be integrated into the Quranic perspective. This integration can be integrated using literature-based research using a descriptive-qualitative method. Hydrocarbon is one of the chemical compounds that exist in the body of living things. Hydrocarbon compounds consist of the elements H, C, O and several other elements. This has been listed in the Quranic verses such as in surah Ar-Rahman verse 14, surah Al-Hijr verse 28, surah Ash-Shaffaat verse 11, surah Al-Imran verse 59. The results obtained from this study should be grateful for the signs of chemistry that have been listed in the Quran and the benefits of hydrocarbons in everyday life.